Development Of A Silver Nanocluster Probe Against Foxp3 For Live Tregs Sorting : Using MCF-7 As A Model - Lee, Shin Yong (2018)
DNA-templated silver nanocluster (AgNC), a new promising fluorescence probe has been gaining importance in recent years. Owing to their special properties such as small in size, photostable and water-soluble, these fluorescence probes are favourable for many diagnostic applications. Due to these advantages, these AgNCs were adapted to develop a method for the identification of regulatory T cells (Tregs) through an intracellular transcription factor called forkhead box P3 (Foxp3). Tregs are crucial mediators of immune homeostasis, exerting suppression on effector cells in autoimmune diseases and promoting the cancer growth.